DEVELOPING STRATEGIC EMPLOYEE GREEN BEHAVIOR SCALE FOR MALAYSIAN INDUSTRY - Mukapit, Mukhiffun (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this paper is to report the development of Strategic Employee Green Behavior Scale (SEGBS) to measure standard green attitudes in workplace. There are very limited instruments that can measure the standard of employee green behavior (EGB) in the workplace. Therefore, eight steps suggested by previous scholar were followed to develop an instrument named SEGBS. The instrument’s reliability, face validity, content validity, and exploratory factor analysis were done. There are 22 items in the first stage of SEGBS development but only 17 items left in the final version of SEGBS.A pilot study was conducted among the ISO14001 certified company’s employees; result indicated a high reliability value. This demonstrated that SEGBS can be used to measure green behavior in a workplace.